2017
DOI: 10.1590/1807-57622016.0633
|View full text |Cite
|
Sign up to set email alerts
|

A satisfação do usuário com a atenção primária à saúde: uma análise do acesso e acolhimento

Abstract: This study aimed to analyze user satisfaction with access and care in Primary Health Care (PHC) based on non-urgent demand for emergency services. 28 non-urgent users of emergency services were intentionally interviewed across five health districts in the city of Riberão Preto in São Paulo State. These users had been treated in PHC at least once in the previous six months prior to data collection aimed at evaluating the services. Content analysis was used to analyze the interviews. The results showed there to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
70

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 15 publications
1
17
0
70
Order By: Relevance
“…Undoubtedly, some of the reasons why teamwork is so strongly emphasized in the interprofessional perspective are patient safety, integrality of healthcare, humanization of practices, and the promotion of workers' comfort and wellbeing 5 . Interprofessionality increases care safety, reducing risks, errors and damages; contributes to the satisfaction of health needs, introducing disease prevention and health promotion actions with precision and on the right time; and enhances users' satisfaction and comfort, which reflects on user embracement, integral care, and patients' adherence to the prescribed/oriented treatment or care plan 6 . Therefore, we must strongly defend teamwork, question teamwork, struggle for permanent health education, and claim for teaching-service-management-participation integration.…”
Section: The Inescapable Supervene: "Inter" Makes New Words and Exprementioning
confidence: 99%
“…Undoubtedly, some of the reasons why teamwork is so strongly emphasized in the interprofessional perspective are patient safety, integrality of healthcare, humanization of practices, and the promotion of workers' comfort and wellbeing 5 . Interprofessionality increases care safety, reducing risks, errors and damages; contributes to the satisfaction of health needs, introducing disease prevention and health promotion actions with precision and on the right time; and enhances users' satisfaction and comfort, which reflects on user embracement, integral care, and patients' adherence to the prescribed/oriented treatment or care plan 6 . Therefore, we must strongly defend teamwork, question teamwork, struggle for permanent health education, and claim for teaching-service-management-participation integration.…”
Section: The Inescapable Supervene: "Inter" Makes New Words and Exprementioning
confidence: 99%
“…In this context, in the perspective of health organizations, as in other business segments, the implementation of quality of service assessment practices, client-centered, using instruments to measure their satisfaction, has been growing, both in the public and private sectors, in many countries around the world, especially in developing countries such as Turkey, India, Saudi Arabia, and Brazil. [12][13][14][15] In Brazil, the incipient culture of evaluating the results of healthcare services can still be considered fragile, since auditing, being the most used, is focused on costs and financial aspects, although some changes have been occurring in this context, with hospital accreditation, where it is necessary to implement and maintain certain quality standards in the result of the service, such as client satisfaction. 16 These aspects, allied to the understanding that the nurse manager should direct their actions to make them compatible with the organizational objectives and client needs, with view to improving nursing care, will promote both professional and organizational growth.…”
Section: Discussionmentioning
confidence: 99%
“…24 Studies that assessed satisfaction in public service attendance found fragility of humanization of care due to deficiencies in reception and communication, contributing to client dissatisfaction. 14,15,22 Thus, it was evident that the client's wishes, which are considered obvious or even elementary, should not be neglected, since the non-fulfillment of these wishes may trigger dissatisfaction and compromise the quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…A baixa qualidade da APS pode estar relacionada a insatisfação dos usuários quanto a falta de resolutividade de seus problemas, demora no atendimento, dificuldade de acesso a especialistas e a tecnologias duras, falta de integração entre os serviços de saúde, acolhimento a demanda espontânea deficitário (ARRUDA;BOSI, 2017;BARATIERI et al, 2017;GOMIDE et al, 2017). Estes fatores de insatisfação levam os usuários a procurarem outros serviços de saúde para situações sensíveis a APS, como os pronto atendimentos, o que causa superlotação desses serviços, aumento de custos para o sistema e redução da resolutividade (BARATIERI et al, 2017;GOMIDE et al, 2017).…”
Section: Discussionunclassified